Literature Review: The Effectiveness Of Brown Rice Diet As Nonpharmacological Nutritional Therapy In Type 2 Diabetes Mellitus Patients - Andi Nur Azizah Alifuddin; Hasan Hasan; Pratiwi Nasir Hamzah (International Journal of Health Engineering and Technology, 2026)
Type 2 diabetes mellitus is a global health problem with a high prevalence in Indonesia and requires comprehensive management, including non-pharmacological nutritional therapy. The choice of carbohydrate sources plays an important role because white rice has a high glycemic index, while brown rice has a lower glycemic index and contains fiber and bioactive compounds that have the potential to help control blood glucose. Therefore, this study aims to determine the nutritional content of brown rice that is relevant to the management of type 2 diabetes, to analyze the effect of brown rice consumption on glycemic control in patients with type 2 diabetes, to determine the effect of a brown rice diet on other metabolic parameters such as body weight, lipid profile, and insulin sensitivity, and to summarize the scientific evidence related to the potential of brown rice as an alternative dietary intervention for patients with type 2 diabetes. This study used a literature review method with a narrative review design. The results of the study showed that brown rice has nutritional content that is relevant to the management of type 2 DM, especially fiber, vitamins, minerals, and bioactive compounds that support improved glucose metabolism. The application of a brown rice diet contributes to improved glycemic control, as indicated by a decrease in fasting blood glucose, postprandial glucose, and HbA1c. In addition, brown rice consumption also has a positive impact on other metabolic parameters, including improved lipid profile, insulin sensitivity, and potential weight control. Overall, brown rice has the potential to be a healthier alternative source of carbohydrates and is applicable as part of non-pharmacological nutritional therapy in patients with type 2 diabetes. It can be concluded that a brown rice diet is an effective and safe non-pharmacological nutritional intervention to support the management of type 2 DM through improved glycemic control and metabolic parameters, making it a recommended alternative carbohydrate source in the patient's diet.